Extraction of betacyanin from Bougainvillea glabra bract and the adsorption onto fibres - Nur Athirah, Sabarudin (2018)
The importance of using natural dyes is increasing worldwide. This is due to the perception of increased environmental and health risks associated with the processing and use of synthetic dyes. Bougainville glabra is known as a red-violet flower garden that contains betacyanin, a betalain pigment. However, the use of Bougainvillea glabra as a natural colouring of textiles is still unknown because of the lack of information on the compatibility in textile dyeing. This research carried out the extraction process of betacyanin from Bougainvillea glabra bracts and the adsorption of the dyes on the fibres. The focus of this study was to find the best dye extraction condition using Response Surface Methodology (RSM) and to determine the adsorption isotherm of dyes on the fibres. In order to determine the best condition of extraction process, one factor at time (OFAT) was studied that is pH (1.0, 4.0, 7.0, and 10.0), solid-liquid ratio (5:100, 7:100, 9:100, 11:100, 13:100, and 15:100) and extraction time (0-180 min) using solid-liquid extraction process. Colour intensity of the dyes and the functional groups of the samples were analyzed using UV-Vis Spectrophotometer and Fourier Transform Infra-Red Spectroscopy (FTIR). The determination of the effects initial concentration of dye and contact time for the adsorption process was studied. The findings have shown that extraction process was better in acidic condition at pH 4.0 than in alkaline, with solid-liquid ratio (SLR) of 11:100. The equilibrium time was achieved after 60 min of extraction process begins. The optimization process revealed that the best condition for betacyanin dye extraction was at 10:100 solid-liquid ratio (SLR) and extraction time of 60 min. From the results, it was estimated that 100 gram of bract can produce about 68.12 g of betacyanin. For adsorption process, spun silk has the highest affinity in retaining the dye compared to rayon and polyester-cotton. The adsorption process tells that spun silk is favourable to be dyed with natural dye compared to the synthetic fibre. The application of the isotherm model in predicting the adsorption capacity of natural dye shows that Freundlich model was fitted better than Langmuir model for describing the interaction between the dye and the fibres.